INTEGRALIDADE DA ATENÇÃO NA SAÚDE DA FAMÍLIA: elenco de serviços ofertados em São Luís - Soares, Walquíria Lemos Ribeiro da Silva (2014)
This study sought to understand Comprehensive care in the Family Health Strategy from the services, on a capital of Brasil, from the perspective of users, managers and health professionals. Methodology: To achieve the proposed objectives , we analyzed data produced by a research project entitled " Evaluation of the quality of primary care in the National Health System in São Luís, Maranhão services " held from January 2010 to March 2011. The target population consisted of managers, professionals and registered users in the Family Health Strategy in St. Louis The survey instrument used was PCATool - Brazil . Interviewing 882 users, 32 managers and 80 health professionals. Results: According to users, professionals and managers Care item for children got the best availability rate , a mean score between 5 and 6 (satisfactory availability - close to 100 % ). The provision of minor surgery was indicated by the three types of informants - keys as the item less available in basic health units , with scores ranging from 1 to 4, getting 11% to 40 % availability in the Family Health Strategy. Conclusion: The perception on the list of services offered in the strategy showed significant differences between subjects. Professionals and managers, the vast majority of items, rated the best services that users, especially when considering care for children and childhood vaccination. Already in the view of users , the availability of preventive dental education service obtained evaluating critical level. There is need for closer management with users of health in trying to understand their real needs and disabilities